Effect of hydration state on Testosterone and Cortisol responses to training-intensity exercise in collegiate runners - Maresh, C. M.; Whittlesey, M. J.; Armstrong, L. E.; Yamamoto, L. M.; Judelson, D. A.; Fish, K. E.; Casa, D. J.; Kavouras, S. A.; Castracane, V. D. (International Journal of Sports Medicine, 2006)
Exercise intensity powerfully influences testosterone, cortisol, and testosterone : cortisol ratio (T : C) responses to endurance exercise. Hydration state may also modulate these hormones, and therefore may alter the anabolic/catabolic balance in response to endurance exercise and training. This study examined the effect of running intensity on testosterone, cortisol, and T : C when exercise was initiated in a hypohydrated state. Nine male collegiate runners (age = 20 ± 0 y, height = 178 ± 2 cm, mass = 67.0 ± 1.8 kg, body fat % = 9.8 ± 0.7 %, V·O2max = 65.7 ± 1.1 ml · kg-1 · min-1) completed four 10-min treadmill runs differing in pre-exercise hydration status (euhydrated, or hypohydrated by 5 % of body mass) and exercise intensity (70 % or 85 % V·O2max). Body mass, urine osmolality, and urine-specific gravity documented fluid balance; blood samples drawn pre-, immediately post-, and 20 min post-exercise were analyzed for testosterone, cortisol, and T : C. Except for heart rate measured during the 70 % V·O2max trials, heart rate, V·O2, and plasma lactate were similar between euhydrated and hypohydrated conditions for a given intensity, suggesting hypohydration did not measurably increase the physiological stress of the exercise bouts. Furthermore, hydration state had no measurable effect on testosterone concentrations before, during, or after exercise at either intensity. Regardless of exercise intensity, cortisol concentrations were greater during hypohydration than euhydration pre-exercise and 20 min post-exercise. Additionally, T : C was significantly lower 20 min post-exercise at 70 % V·O2max when subjects were initially hypohydrated (T : C = 0.055) versus euhydrated (T : C = 0.072). These findings suggest that depending on exercise intensity, T : C may be altered by hydration state, therefore influencing the balance between anabolism and catabolism in response to running exercise performed at typical training intensities.